Posttraumatic Atlantoaxial Rotatory Dislocation in a Healthy Adult Patient: A Case Report and Review of the Literature - Giuseppe Maida; Eleonora Marcati; Silvio Sarubbo (Case Reports in Orthopedics)
Atlantoaxial rotatory dislocation (AARD) is a rare complication in adults usually leading to pain, spinal cord injury, or death. Clinical and radiological diagnosis is difficult and often delayed. We report a rare case of posttraumatic AARD in a neurological intact 27-year-old male in which initial radiographic evaluation was negative. A computed tomography (CT) scan was promptly done because the patient showed a severe torticollis. Therefore, early diagnosis, immobilisation, and surgical fusion and arthrodesis were performed. After surgery, cervical pain and torticollis were resolved and the patient remained neurologically intact with a CT scan documentation of fusion at the 3-year followup.